2011
DOI: 10.1002/jcb.23263
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent effects of the caspase inhibitor Q‐VD‐OPh on different apoptosis‐related processes

Abstract: The effects of the pan-caspase inhibitor Q-VD-OPh on caspase activity, DNA fragmentation, PARP cleavage, 7A6 exposition, and cellular adhesivity to fibronectin were analyzed in detail in three different apoptotic systems involving two cell lines (JURL-MK1 and HL60) and two apoptosis inducers (imatinib mesylate and suberoylanilide hydroxamic acid). Q-VD-OPh fully inhibited caspase-3 and -7 activity at 0.05  µM concentration as indicated both by the measurement of the rate of Ac-DEVD-AFC cleavage and anti-caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Similar relationship between ROS presence and the extent of apoptosis was documented using pan-caspase inhibitors z-VAD-fmk or Q-VD-OPh (Figure 4(b)). Q-VD-OPh is known to inhibit caspase activity of HL-60 cells already at 2  μ M, while higher concentration of Q-VD-OPh was reported to prevent PARP fragmentation or loss of cellular adhesiveness [49]. In our experiments, 30  μ M Q-VD-OPh completely cancelled DAC + SAHA + ATRA-induced apoptosis and simultaneously almost fully abolished ROS generation.…”
Section: Discussionsupporting
confidence: 52%
“…Similar relationship between ROS presence and the extent of apoptosis was documented using pan-caspase inhibitors z-VAD-fmk or Q-VD-OPh (Figure 4(b)). Q-VD-OPh is known to inhibit caspase activity of HL-60 cells already at 2  μ M, while higher concentration of Q-VD-OPh was reported to prevent PARP fragmentation or loss of cellular adhesiveness [49]. In our experiments, 30  μ M Q-VD-OPh completely cancelled DAC + SAHA + ATRA-induced apoptosis and simultaneously almost fully abolished ROS generation.…”
Section: Discussionsupporting
confidence: 52%
“…When the effects of etoposide are paired with Bcl-2 family disequilibrium it suggests a specific mechanism for the selective clearance of encephalitogenic T cells that we observe in vivo . To test if apoptosis or necroptosis is the primary mechanism of etoposide-mediated cell death in encephalitogenic T cell we utilized the pan-caspase inhibitor Q-VD-OPH to prevent apoptosis (48, 49), and the RIP-1 inhibitor necrostatin to prevent necroptosis (50). We found that when encephalitogenic CD4 + T cells were treated with etoposide in the presence of Q-VD-OPH cell death decreased from the level of etoposide only to the level of vehicle treated cells (Figure 8H).…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the effect of caspase-4 and general caspase inhibition on in vitro network formation as an indicator of the relevance of the selected signaling signature for in vivo vessel formation. To avoid toxic side effects, concentrations of caspase-4 and pan-caspase inhibitors were titrated based on previous studies [18], [19], [23] (Figure S6). Untreated UC-derived ECFCs capable of forming vascular-like networks covering the matrix area after 24 hours were used as a positive control (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Our data also established the as of yet unknown role of the inflammatory caspase-4 in regulating neo-vasculogenesis. We used small molecule caspase-4 (Z-FMK-LEVD) and, as a positive control, pan-caspase (Q-VD-OPh) inhibitors that irreversibly block caspases without cyto-toxicity effect [18], [19], [23], thus verifying the drugability of caspases as targets in this experimental therapeutic application. Whether caspase-4 plays a progenitor cell-specific role in apoptosis-induced proliferation during tissue regeneration remains to be studied [38].…”
Section: Discussionmentioning
confidence: 99%